2021
DOI: 10.1016/j.omtn.2020.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-590-3p derived from cancer-associated fibroblasts confers radioresistance in colorectal cancer

Abstract: Radiotherapeutic resistance is a major obstacle for the effective treatment of colorectal cancer (CRC). MicroRNAs (miRNAs) play a critical role in chemoresistance and radioresistance. Here, we aimed to investigate whether miR-590-3p participates in the radioresistance of CRC. High expression of miR-590-3p and low expression of CLCA4 were found in both CRC tissues and cell lines. CLCA4 was indicated to be a target gene of miR-590-3p. CAF-derived exosomes were extracted and co-cultured with CRC cells, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 45 publications
1
60
0
Order By: Relevance
“…In CRC, the CAFs-derived exosomes have been reported as an important cause of radio resistance of cancer cells by preventing the DNA damage and inhibiting apoptosis and in CRC cells. These results were associated with reduced activities of cleaved-caspase 3 and cleavedpoly (ADP-Ribose) polymerase 1 (PARP) induced by CAFs-derived exosomes [139]. The up-regulated miR-590-3p in CAFs-derived exosomes compared with normal fibroblast-derived exosomes was confirmed to play a critical role in this regulation by targeting at chloride channel accessory 4 (CLCA4) and activating the PI3K/ AKT signaling pathway [139].…”
Section: Therapy Resistancementioning
confidence: 96%
“…In CRC, the CAFs-derived exosomes have been reported as an important cause of radio resistance of cancer cells by preventing the DNA damage and inhibiting apoptosis and in CRC cells. These results were associated with reduced activities of cleaved-caspase 3 and cleavedpoly (ADP-Ribose) polymerase 1 (PARP) induced by CAFs-derived exosomes [139]. The up-regulated miR-590-3p in CAFs-derived exosomes compared with normal fibroblast-derived exosomes was confirmed to play a critical role in this regulation by targeting at chloride channel accessory 4 (CLCA4) and activating the PI3K/ AKT signaling pathway [139].…”
Section: Therapy Resistancementioning
confidence: 96%
“…A recent finding has discovered that cetuximab increases CAFs' EGF secretion, which is sufficient to render neighboring cancer cells resistant to cetuximab in combination with chemotherapy for metastatic CRC patients (Garvey et al, 2020). Moreover, CAFderived exosomal miR-93-5p or miR-590-3p has been shown to rescue CRC cells from radiation-induced apoptosis (Chen et al, 2020(Chen et al, , 2021, and the promoted CRC stemness was demonstrated to account for the radioresistance imposed by CAF-derived exosomes . Thus, these discoveries build a mechanistic connection between CAF-maintained cancer stemness and therapy resistance in CRC.…”
Section: Stemness and Therapy Resistancementioning
confidence: 99%
“…AZGP1 is a useful diagnostic biomarker found in the tissues and serum of Chinese CRC patients and it promotes epithelial-mesenchymal transition (EMT) in colorectal cancer via the filamin A-mediated focal adhesion pathway [44]. Furthermore, other genes associated with MC1R in the PPI, such as MMP7, CLCA4, MS4A12, KRT23, and NFE2L3, have been shown to play a vital role in the progression of CRC [45][46][47][48][49]. Overall, MC1R may be involved in the occurrence and development of CRC by interacting with the above molecules.…”
Section: Discussionmentioning
confidence: 99%